HLA‐DRB1*14:54:09 and ‐DRB1*14:54:10, were identified by next‐generation sequencing in Chinese cord blood donors. (7th December 2020) - He, Yanmin; Tao, Sudan; Chen, Chen; He, Ji; Zhu, Faming
Abstract : The sequences of HLA‐DRB1*14:54:09 and HLA‐DRB1*14:54:10 differ from HLA‐DRB1*14:54:01:01 by one single nucleotide substitution, respectively.